1976
DOI: 10.1152/ajplegacy.1976.231.3.945
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the aldosterone-sodium and -potassium feedback control system

Abstract: This study was conducted to determine the quantitative importance of the aldosterone feedback mechanism in controlling each one of three major factors that have often been associated with aldosterone, namely, extracellular fluid sodium concentration, extracellular fluid potassium concentration, and extracellular fluid volume. To do this, the ability of the body to control these three factors in the face of marked changes in daily sodium or potassium intake was studied under two conditions: 1) in the normal dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

1980
1980
2000
2000

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 0 publications
5
9
0
Order By: Relevance
“…Chronic adrenal insufficiency is associated with hyperkalemia and with a decreased ability to excrete an acute potassium load (5-1 1). Young et al (12)(13)(14) have demonstrated the importance of chronic aldosterone replacement in adrenalectomized dogs in maintaining potassium homeostasis. Thus, restoration of plasma aldosterone in glucocorticoid replete, aldosterone-deficient animals lowers plasma potassium to basal levels and normalizes the relationship between plasma potassium concentration and urinary excretion of potassium.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic adrenal insufficiency is associated with hyperkalemia and with a decreased ability to excrete an acute potassium load (5-1 1). Young et al (12)(13)(14) have demonstrated the importance of chronic aldosterone replacement in adrenalectomized dogs in maintaining potassium homeostasis. Thus, restoration of plasma aldosterone in glucocorticoid replete, aldosterone-deficient animals lowers plasma potassium to basal levels and normalizes the relationship between plasma potassium concentration and urinary excretion of potassium.…”
Section: Introductionmentioning
confidence: 99%
“…On the second control day "Na space (determined by the 3-h dilution of a known amount of "Na given intravenously) Young et al, 1976), and body weight were measured.…”
Section: Methodsmentioning
confidence: 99%
“…The experiments were carried out in six healthy mongrel dogs whose weight averaged 22 kg. Chronically implanted arterial and venous catheters were placed as described previously (Cowley, Liard & Guyton, 1973Young et al, 1976). Following surgical recovery the dogs were housed in metabolic cages and fed a controlled diet containing 10 mmol/day of sodium and 30 mmol/day potassium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aldosterone is increased after exercise [31]. Among the factors known to regulate aldosterone secretion, K is considered one of the most potent [32]. The observed decline in serum K. may therefore have mediated the more rapid decline of aldosterone observed in the CHO condition.…”
Section: Hormonal Responsesmentioning
confidence: 99%